Exile from the actual: Delmore Schwartz and the difficult inheritance of T. S. Eliot. - Richardson, Scott. (University of Ottawa (Canada), 1997)
In his earliest work, American writer Delmore Schwartz takes his cue from the writings of T. S. Eliot. Schwartz's experience is representative of his generation's experience, but his intense devotion to Eliot's work and person is highly idiosyncratic. Eliot's legacy soon becomes troublesome. Schwartz watches Eliot create a distant, authoritative persona in exile, yet as he narrates his own family's stories of emigration, Schwartz wonders if one can ever truly transcend determined identity. Exile for Schwartz is primarily an attitude toward experience. Eliot exemplifies that attitude. We thrives on the distance of exile; his poetry is seen by Schwartz as a striving for ideal order. Schwartz begins during the 1940s and 50s to mistrust such idealism and find value in the disorderly actuality of American life. He looks to new artistic heroes like James Joyce to replace Eliot. The new aesthetic of celebration, however, coexists uneasily with Schwartz's instinct for criticism.
Keywords: Literature, Modern.